P4.21 Side chicks, thots and side dicks: typologies and drivers of concurrent partnerships among people of black caribbean ethnicity in england and implications for sti prevention and partner notification. (8th July 2017) - Mercer, Cath; Wayal, S; Vl, Gilbart; Garnett, E; Lj, Sutcliff; Weatherburn, P; Hughes, G
Abstract : Introduction: In Britain, STI diagnoses rates are highest among black Caribbeans compared to other ethnic groups. The prevalence of concurrency is also high in this population. Concurrent partnerships, (i.e. having sexual partners overlapping in time), can enhance the rate and speed of STI transmission. We explored typologies and drivers of concurrency in black Caribbeans in England and considered their implications for STI prevention. Methods: Using purposive sampling, we recruited people of black Caribbean ethnicity aged ≥15 years from community settings and STI clinics. Audio-recorded 4 focus group discussions (n=28 participants) and 24 in-depth interviews were conducted between June 2014-Dec 2015 using topic guides. Data was transcribed, managed using NVivo software and analysed using thematic framework to identify patterns of concurrent partnerships and condom use, and reasons for concurrency. Results: 32 women and 20 men (age range: 15–70 years) identifying as heterosexual participated. Open, situational, and experimental concurrent partnerships were commonly reported. Open concurrent partnerships involved a person having a main sexual partner and, in the case of men, additionally having sex with other "side chicks" or "thots", and in the case of women, "side dicks" . Situational partnerships involved having a sexual relationship with an ex-partner, especially with someone with whom they had had a child, while having another main sexual partner. These types of partnerships were usually long-term, and condoms were less likely to be used due to emotional attachment, if a co-parent was single and then condomless sex was perceived as a way to "entice" the partner back, or due to the relationship being founded on sexual pleasure. Usuallypeople were aware of the concurrent nature of these partnerships. Experimental concurrent partnerships, commonly reported by single participants, were usually short term, and mostly involved condom use. These were fuelled by lack of readiness to settle with a single partner, or trying to figure out the type of partner they may want to settle with. Other commonly reported reasons for concurrency were low self-esteem at an individual level. At a socio-cultural level, although concurrency was frowned upon, it was perceived as " a Black Caribbean thing" with references being commonly made in certain types of popular music and dance among black Caribbeans, changing norms of relationships in an era where you can "order sex via app", peer pressure, and a normalisation of concurrency on social media, especially among men. Conclusion: Among black Caribbeans, the different types and contexts of concurrent partnerships can have implications for STI prevention. Awareness of being in a concurrent partnership could potentially facilitate uptake of interventions including condom use, partner notification, and reduce the risk of re-infection. In addition, such interventions should address broader sociocultural factors influencing risk behaviour including the impact of media.